A review of orbital-scale monsoon variability and dynamics in East Asia during the Quaternary. (15th July 2022) - Sun, Youbin; Wang, Ting; Yin, Qiuzhen; Lyu, Anqi; Crucifix, Michel; Cai, Yanjun; Ai, Li; Clemens, Steven; An, Zhisheng
Abstract: Quaternary monsoon changes in East Asia have been extensively investigated by proxy records from continental and marine archives. However, these proxy indicators often show controversial characteristics in terms of trends and rhythms, leading to perplexedunderstanding of orbital-scale monsoon dynamics. Here we review the orbital-scale monsoon variability and dynamics in East Asia by comparing multiple proxies from loess, lake, speleothem, and marine records with the HadCM3 modeling result. Evolutionary power spectra of loess grain size and sea surface temperature exhibit a remarkable shift from 41- to 100-kyr cycles across the mid-Pleistocene transition (MPT), whereas other proxy records (e.g. δ 13 C of loess carbonate, pollen concentration in lake sediments, and magnetic mineral compositions in marine sediments) display distinct and persistent precession cycles through the Quaternary, along with strong 100-kyr cycles after the MPT. Simulations with the HadCM3 climate model reveal that the effects of orbital parameters, ice volume, and CO2 concentration on the temperature, precipitation, and southerly winds are seasonally and spatially different in East Asia. In the summer season, orbitally induced insolation plays a dominant role in driving changes in these three climate variables except for summer precipitation in south China (20-30°N), whilst annual changes in precipitation and temperature are jointly affected by insolation, ice volume, and CO2 . Proxy-model comparison suggests that several land-based proxies are sensitive to changes in summer precipitation, annual precipitation, and annual temperature, though their responses to astronomical, ice, and CO2 forcing being quite different between north and south China. Our proxy-model comparison reveals that diverse expression of Quaternary climate periodicities was provoked by different sensitivities of marine and terrestrial proxies to seasonal and/or annual changes in precipitation and temperature, and by different responses of temperature and precipitation to insolation and ice/CO2 forcing. We suggest that understanding of Quaternary climate change can be deepened by further comparison of quantitatively reconstructed paleotemperature and precipitation data with high-resolution regional climate modeling results. Highlights: Quaternary monsoon variability has been addressed by synthesizing multiple proxies from terrestrial and marine arcives. The effects of insolation, ice volume, and CO2 on climate elements are seasonally and spatially different in East Asia. Proxy-model comparison suggests that insolation, ice, and CO2 changes jointly affect rbital-scale monsoon variability.. Future research should focus on comparison of quantitative paleotemperature and precipitation data with model results.